Nosocomial mucormycosis of the thigh. (2021) - Boodman, Carl; Cheng, Matthew P.
Abstract: We describe a case of nosocomial mucormycosis of the thigh in an immunocompromised patient admitted with COVID-19 acute respiratory distress syndrome.